Climate Parameter Uses as Indices For Assessment of Climate Change and Water Balance in Erbil Sub-Basin North –Iraq - Hamed , Masoud Hussein (Iraqi Journal of Science, 2023)
The main goal of this study was to assess the climatic parameters in a valuable basin in northern part of Iraq, Erbil central sub-basin. Rainfall, relative humidity, temperature, evaporation, sunshine duration, and wind speed are the climate variables used in this study. The investigated periods (1980-2021) of Erbil meteorological data were used to assess the climatic and drought conditions in the studied basin. The results show a noticeable drop in relative humidity and rainfall over the past two decades, as well as a considerable rise in temperature and evaporation. The mean annual rainfall was 416mm, relative humidity is 48.74% used as term of water availability, and mean annual temperature is 22°C, total annual evaporation was 2257.59mm, sunshine duration was 8.2 hours/day, and wind speed is 1.7m/s were used as water loss elements. Kharufa technique was applied to determine the potential evapotranspiration, water deficit and water surplus periods. According to the findings, there is a total of 2257.59 mm of potential evapotranspiration, water excess, and water deficit, 89.22mm, and 1953.95mm, respectively. Annual surface runoff was 37.85mm, and annual recharge from rainfall was 13.07%. Alkubaisi classification for climate type were utilized to identify the Erbil central sub-climatic basin’s type. The results showed that the climate is arid based on the initial categorisation, moist to sub-arid according to the second cataloguing, and dry according to the third cataloguing.